1987
DOI: 10.1016/0167-188x(87)90076-0
|View full text |Cite
|
Sign up to set email alerts
|

Capacity analysis of two-stage production lines with many products

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore the buffer content will sometimes increase and sometimes decrease. In De Koster [9] it is shown that the throughput (and also the distribution of the buffer content and many other line characteristics) of a two-stage line is determined almost completely by the buffer fluctuations. Actually only the first and second moments of buffer increase and buffer decrease and the expected length of an increase and a decrease period suffice for an adequate approximation.…”
Section: Approximation Of Parallel Machines In Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the buffer content will sometimes increase and sometimes decrease. In De Koster [9] it is shown that the throughput (and also the distribution of the buffer content and many other line characteristics) of a two-stage line is determined almost completely by the buffer fluctuations. Actually only the first and second moments of buffer increase and buffer decrease and the expected length of an increase and a decrease period suffice for an adequate approximation.…”
Section: Approximation Of Parallel Machines In Seriesmentioning
confidence: 99%
“…The transitions between the four machine states (c 1, v 1, v 2, v2) of PU 1 in How this choice has to be made is explained in [9]. In the determination of the 9 parameters we have only 6 binding equations.…”
Section: Approximation Of Parallel Machines In Seriesmentioning
confidence: 99%
See 1 more Smart Citation